Development of high-temperature superconductor cables for high direct current applications - Preuß, Alan (Karlsruher Schriftenreihe zur Supraleitung, 2021)
A design process for HTS DC cables was developed for high current applications. Based on the design process, a 35 kA HTS DC cable demonstrator was developed. The superconducting elements of the demonstrator were manufactured and tested individually at 77 K. Afterwards, the demonstrator cable was assembled and tested at 77 K. The assembled demonstrator successfully reached 35 kA at 77 K and self field conditions.